The appraisal of costs in the proceedings of mortgage enforcement (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
In the mortgage foreclosure process following the auction and award of the mortgaged and property, the debtor continues to be liable not only for the ordinary interest loan, that is not settled for the value obteined with the award, but a significant amount of default interest and court costs, which typically exceed 50% of the principal claimed. In this study we analyze as such excess can and should be mitigated by proper control of the amounts presented by the mortgagee in respect of legal costs, thus avoiding abuses covered in the usual situation of procedural default of the mortgagor and subsequent lack of contest.
Keywords: appraisal of costs; mortgage enforcement; Court Clerk.